Tectonic and Regional Structure of Seram and the Banda Arc - Hill, Kevin C. (Berita Sedimentologi, 2012)
Seram and the Banda Sea lie between the passive margin tectonics of Australia’s Northwest Shelf and the active margin tectonics of New Guinea, both of which have played an important role in the structure, facies distribution and hydrocarbon prospectivity of the area.A restored cross section across Seram and a 3D model reconstruction of the Miocene evolution of the Banda Arc reveal the history of the area. The Proto-Banda Sea is considered to have formed in the Permian, including a marginal basin with Permian oceanic crust. Extension was terminated by Triassic orogenesis in New Guinea supplying vast amounts of Triassic detritus (Kanikeh) to the stretched Banda margins. In the Late Triassic, the sediment supply was diminished in part due to the renewed onset of extension along the New Guinea margin. It is notable that the Triassic orogeny was very similar to the Miocene to Recent orogeny in New Guinea. As Triassic sediment supply was reduced, carbonate banks were locally built up (Manusela reservoir) surrounded by starved source rock facies. The margin subsided in the Jurassic and was starved of sediment until the Tertiary when renewed tectonic activity in New Guinea supplied distal carbonates and marls, mainly in the Miocene. Around 10 Ma, the Indonesian Arc impinged on the Permian oceanic lithosphere of the Proto Banda Sea, which was then rapidly subducted, sinking under its own weight. The Arc advanced rapidly eastwards towards Timor and Seram, generating a collisional margin in Timor, but a strongly transpressional margin in Seram. The first phase of collision in Seram at ~6 Ma involved overthrusting of an accretionary prism, largely comprising Kanikeh sediments, but also some oceanic fragments. The second phase of orogenesis in Seram involved thrusting of the continental margin beneath the overthrust, creating highly fractured antiformal stacks in the Manusela encased in Kanikeh seal and source rocks, as in the Oseil oilfield. To the east an imbricate thrust zone has formed in the Cretaceous and Tertiary sequences which is now impinging on the Misool-Onin Arch.